QRIS Payment Transactions as a Strategy for Enhancing the Revenue of Micro, Small, and Medium Enterprises (MSMEs): A Case Study of Sidorejo Subdistrict, Medan Tembung District - Eka Milia Ningrum; Tri Inda Fadhila Rahma; Nurul Jan (Jurnal Bisnis dan Manajemen, 2025)
Abstract: Economic growth is a key indicator of economic development progress in a region. Technological innovation can serve as a catalyst to increase the turnover of Micro, Small, and Medium Enterprises (MSMEs) by identifying suitable strategies for a given area. Therefore, this study aims to determine strategies that can enhance MSME turnover through Quick Response Code Indonesian Standard (QRIS) payment transactions. The research method employed is descriptive qualitative with SWOT analysis. Based on the IFAS calculation, the score is 2.88, where the combined strengths and weaknesses yield a positive value (X-axis). Meanwhile, the EFAS calculation result is 2.68, with the combined opportunities and threats also yielding a positive value (Y-axis). Consequently, the results demonstrate that the study yields positive outcomes and is applicable for increasing MSME turnover within a region.